Institutional and contextual obstacles to sexuality education policy implementation in Uganda. Issue 1 (2nd January 2020) - Ninsiima, Anna B.; Coene, Gily; Michielsen, Kristien; Najjuka, Solome; Kemigisha, Elizabeth; Ruzaaza, Gad Ndaruhutse; Nyakato, Viola N.; Leye, Els
ABSTRACT: The successful implementation of sexuality education policy for young people has been shown to depend on a sound legislative and institutional framework. This article shows that both institutional factors and contextual obstacles have impeded the implementation of sexuality education policy in Uganda. Qualitative research techniques were employed in the form of systematic document reviews and extensive field-work with 64 participants, of which 32 were in-depth interviews with policymakers and key stakeholders in Kampala and Mbarara districts. In addition, four focus group discussions (n = 32) were conducted with teachers. The analysis was carried out thematically and manually, using open and axial coding. It was found that policy success was primarily limited by two broad factors: firstly, by institutional weaknesses such as a lack of capacity, inadequate financial commitment, poor coordination between relevant ministries and ineffective monitoring, and regulatory frameworks; secondly, by social, cultural and religious norms that give informal power to religious and cultural leaders. Two strategies are suggested as potential ways forward: (i) a commitment to both the human and financial resources needed to monitor adolescent sexual, and reproductive health programmes, but more importantly (ii) the initiation of negotiations with cultural and religious leaders to yield more positive outcomes.